Ultrasound application for the decontamination of roselle (Hibiscus sabdariffa L.) seeds: Influence on fungal inhibition and seed quality - Aminallah Tahmasebi; Ashkan Asgari; Somayeh Bakhshi; Amir Ghaffar Shahriari; Chul Won Lee (Ultrasonics Sonochemistry, 2023)
Seed decay is a major problem caused by pathogens that adversely affect seed yield and quality in agricultural production. Herein, the effect of 28 KHz ultrasound treatment for 20, 40 and 60 min and 1.5% sodium hypochlorite solution for 20 min was assessed for the decontamination of roselle (Hibiscus sabdariffa L.) seeds. In addition, seed germination indices, seedling growth traits, total phenolic content and the activity of defense-related enzymes, viz. peroxidase, superoxide dismutase, catalase and malondialdehyde were measured in the treated seeds. An isolate of Fusarium solani was obtained from roselle seeds and identified as the causal agent of roselle seed rot based on morphological and molecular characteristics. After six days of seed storage, the microbial infection caused the highest seed rot in the control seeds on the average of 56.67%, whereas ultrasound treatment for 60 min could remarkably reduce the seed decay by 3.33%. At the end of seed storage, the fungal load showed the highest (7.72 Log CFU ml−1) and lowest (6.99 Log CFU ml−1) rates in the control and ultrasound treatment for 60 min, respectively. Total phenolic content was significantly increased in ultrasound treatment for 60 min compared to control and sodium hypochlorite treatments. Moreover, the activity of peroxidase, superoxide dismutase and catalase was noticeably improved in ultrasound treatment for 60 min. Furthermore, ultrasound treatment did not show any adverse effects on seed germination indices and seedling growth traits of the roselle plants. Overall, ultrasound treatment for 60 min could effectively decrease roselle seed decay and the fungal load without changing seed and seedling quality.